Ovarian Ectopic Pregnancy in Adolescence - Gonçalves Andrade, A (2015)
Ovarian pregnancy is one of the rarest types of extrauterine pregnancy. Its preoperative diagnosis remains a challenge since it presents quite similarly to tubal pregnancy and complicated ovarian cysts. Although in most cases, histology is necessary to confirm the diagnosis, we present an ovarian pregnancy in a teenager, correctly diagnosed during ultrasound examination.